1999
DOI: 10.1152/jappl.1999.86.5.1728
|View full text |Cite
|
Sign up to set email alerts
|

Validity of methods of body composition assessment in young and older men and women

Abstract: We examined the validity of percent body fat (%Fat) estimation by two-compartment (2-Comp) hydrostatic weighing (Siri 2-Comp), 3-Comp dual-energy X-ray absorptiometry (DEXA 3-Comp), 3-Comp hydrostatic weighing corrected for the total body water (Siri 3-Comp), and anthropometric methods in young and older individuals (n = 78). A 4-Comp model of body composition served as the criterion measure of %Fat (Heymsfield 4-Comp; S. B. Heymsfield, S. Lichtman, R. N. Baumgartner, J. Wang, Y. Kamen, A. Aliprantis, and R. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
102
5
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 37 publications
8
102
5
1
Order By: Relevance
“…The mean difference was 4.6 %BF. Clasey et al (1999) also found the same equation to significantly underestimate %BF in younger (mean difference ¼ 2.4%) and older women (mean difference ¼ 7.9%) compared to a 4C model. Similarly, Hart et al (1993) and Bottaro et al (2002) found other skinfold equations to underestimate %BF compared to DXA in a group of adults and Hispanic women, respectively.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…The mean difference was 4.6 %BF. Clasey et al (1999) also found the same equation to significantly underestimate %BF in younger (mean difference ¼ 2.4%) and older women (mean difference ¼ 7.9%) compared to a 4C model. Similarly, Hart et al (1993) and Bottaro et al (2002) found other skinfold equations to underestimate %BF compared to DXA in a group of adults and Hispanic women, respectively.…”
Section: Introductionmentioning
confidence: 64%
“…Unfortunately, it is not realistic to perform this type of assessment on any great number of subjects. Thus, researchers have been forced to develop field methods (ie, anthropometric equations) mostly from the 2C model despite significant differences in %BF values between it and the 4C model (Withers et al, 1998;Clasey et al, 1999). Differences of 3-4 %BF, attributed mostly to variations in body water, adipose tissue, and bone density have been observed (Bakker & Struikenkamp, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…It allows for a rapid, noninvasive estimation of body fat with minimal radiation exposure (van der Ploeg et al, 2003) and has the advantage of a three-compartment model of body composition that quantifies fat, soft lean tissue and bone mineral. DXA has been validated against various multicompartment models in young (Prior et al, 1997;Clasey et al, 1999), old (Clasey et al, 1999) and a wide age range of healthy sedentary individuals (Gallagher et al, 2000). Nevertheless, the validity of the method has remained subject to question, particularly with regard to concerns over tissue thickness and hydration levels (Laskey et al, 1992;Jebb et al, 1995;Pietrobelli et al, 1996Pietrobelli et al, , 1998Wang et al, 1998;van der Ploeg et al, 2003), which will vary between individuals and groups of subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Two other studies (Modlesky et al, 1996;Withers et al, 1997) have reported significant overestimations in hydrodensitometrically determined %BF in weight-trained subjects. While other investigators (Friedl et al, 1992;Cote & Adams, 1993;Penn et al, 1994;Siconolfi et al, 1995;Prior et al, 1997;Visser et al, 1997;Goran et al, 1998;Clasey et al, 1999) have not found significant mean differences, their data have displayed large individual differences between two-and multicompartment techniques. This was exemplified by the hydrodensitometric data of Prior et al (1997) that contained deviations from their four-compartment values ranging from À8.1 to 8.5%BF in young men and women.…”
mentioning
confidence: 83%